2016
DOI: 10.1016/j.contraception.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on the pharmacokinetics of levonorgestrel-based emergency contraception: single and double dosing

Abstract: Objective To determine if differences exist in the pharmacokinetics (PK) of levonorgestrel-based emergency contraception (LNG-EC) in obese and normal body mass index (BMI) users and test whether doubling the dose of LNG-EC in obese women increases total and free (active) LNG serum concentrations. Study design Healthy, reproductive-age women with obese and normal BMIs received 1.5 mg LNG orally (ECx1) and then in a subsequent menstrual cycle, the obese group also received 3mg LNG (ECx2). Dosing occurred durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 20 publications
5
39
1
1
Order By: Relevance
“…A study210 of the pharmacokinetics of LNG-EC in five women with obesity and five women without obesity demonstrates that obesity adversely impacts maximum serum concentrations of LNG. The authors postulate that this may explain a reduction in effectiveness of LNG-EC in women with obesity.…”
Section: Suitability Of Contraceptive Methods For Women Who Are Ovementioning
confidence: 99%
See 1 more Smart Citation
“…A study210 of the pharmacokinetics of LNG-EC in five women with obesity and five women without obesity demonstrates that obesity adversely impacts maximum serum concentrations of LNG. The authors postulate that this may explain a reduction in effectiveness of LNG-EC in women with obesity.…”
Section: Suitability Of Contraceptive Methods For Women Who Are Ovementioning
confidence: 99%
“…Studies testing the effectiveness of double-dose LNG-EC are in progress, but its effectiveness is unknown. However, 3 mg LNG-EC is well tolerated and pharmacokinetic data210 suggest its potential ability to prevent unintended pregnancy more effectively than 1.5 mg LNG-EC in women weighing >70 kg or with a BMI >26 kg/m 2 .…”
Section: Suitability Of Contraceptive Methods For Women Who Are Ovementioning
confidence: 99%
“…More recently, a pooled analysis of randomised controlled trials of LNG conducted by WHO ( n = 6873) reported higher pregnancy rates among women with obesity compared with women of normal weight (although this was only statistically significant with regression analysis and adjustment for several factors) . There are also pharmacokinetic data indicating that LNG takes a longer time to achieve steady‐state levels in women with obesity compared with those of normal BMI, which can be overcome by doubling the dose of LNG . Conversely, the pharmacokinetics of UPA is not affected by obesity .…”
Section: Effectiveness Of Ecmentioning
confidence: 99%
“…Ellero et al [25] found very low levels of the mRNA for 20 xenobiotic-metabolizing CYP genes in subcutaneous and visceral white adipose tissue of women. It is thus of great interest that Edelman et al [26] examined the plasma concentrations of LNG during the first 2.5 h after giving 1.5 mg doses of LNG (Next Choice™; Activis) to 5 obese (BMI ≥30 kg/m 2 ) and 5 normal-weight women. They had also measured unbound LNG and SHBG concentrations.…”
Section: Ocsmentioning
confidence: 99%
“…Thus, SHBG binding of LNG and EE may have a protective role for some tissues. A recent publication in this journal [40] has largely endorsed the free drug hypothesis in arguing for the relevance of measurements of unbound LNG concentrations in obese women [26]. However, as reviewed by Smith et al [41], there are many exceptions to the application of the free hormone hypothesis.…”
Section: Role Of Protein Bindingmentioning
confidence: 99%